2005
DOI: 10.1300/j039v09n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Prison Pups: Assessing the Effects of Dog Training Programs in Correctional Facilities

Abstract: During the past twenty-five years, the number of prison programs in which inmates train dogs has increased rapidly. There are no comprehensive data on the prevalence of such programs, but they are in existence in at least twenty U.S. states, Canada, Australia, New Zealand, and Italy. Though extremely popular among both administrators and inmates, we have only anecdotal accounts to assess the effects of dog training by inmates. Such programs appear to have the potential to break down barriers of fear and mistru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 10 publications
2
44
1
Order By: Relevance
“…For example, in response to research that suggests that some colours can be more soothing than others, a prison in Dallas County painted the prison walls pink in an attempt to improve the prison environment (Borghese 2006). Other institutions have introduced pets (such as puppies and birds) to help offenders learn basic social skills (Britton & Button 2006;Fournier et al 2007;Lindemuth 2007). Most of these experiments have not, however, been subject to any formal evaluation and, as such, conclusions about their effectiveness cannot be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in response to research that suggests that some colours can be more soothing than others, a prison in Dallas County painted the prison walls pink in an attempt to improve the prison environment (Borghese 2006). Other institutions have introduced pets (such as puppies and birds) to help offenders learn basic social skills (Britton & Button 2006;Fournier et al 2007;Lindemuth 2007). Most of these experiments have not, however, been subject to any formal evaluation and, as such, conclusions about their effectiveness cannot be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…One of the strongest areas of research evidence has been the positive physiological results from pet ownership with regard to lowering blood pressure, cholesterol, and assisting with weight reduction (Britton & Button, 2006). The presence of a pet has proven to be more beneficial to reduce stress than a spouse or a friend.…”
Section: Pet Therapy In Correctional Institutionsmentioning
confidence: 99%
“…These types of training-based therapies have been hypothesized to ultimately improve the patient's mental health, either via the interaction with the animal itself, or via improvement on several key features that impact the outcomes of psychotherapy. Specifically, research has found that when individuals learn to train and care for difficult-to-adopt shelter dogs, they demonstrate increased interest and participation in meaningful activities, decreased feelings of detachment/estrangement from others, expanded range of affect, and an increased future-oriented outlook (Britton and Button 2006;Harkrader et al 2004;Messent 1983). For example, programs in which individuals experiencing emotional numbing are taught to train difficult-to-adopt shelter dogs (i.e., dogs with behavioral/psychological challenges including anxiety, fear, and hyperactivity) have found positive results for the human participants with respect to increases in social skills (Davis and Bunnell 2007;Fournier et al 2007;Turner 2007), patience (Britton and Button 2006;Furst 2006), empathy (Strimple 2003), compassion (Harbolt and Ward 2001), and parenting skills (Britton and Button 2006;Turner 2007).…”
Section: Human-animal Interaction (Hai) For Military Personnel and Vementioning
confidence: 99%
“…Specifically, research has found that when individuals learn to train and care for difficult-to-adopt shelter dogs, they demonstrate increased interest and participation in meaningful activities, decreased feelings of detachment/estrangement from others, expanded range of affect, and an increased future-oriented outlook (Britton and Button 2006;Harkrader et al 2004;Messent 1983). For example, programs in which individuals experiencing emotional numbing are taught to train difficult-to-adopt shelter dogs (i.e., dogs with behavioral/psychological challenges including anxiety, fear, and hyperactivity) have found positive results for the human participants with respect to increases in social skills (Davis and Bunnell 2007;Fournier et al 2007;Turner 2007), patience (Britton and Button 2006;Furst 2006), empathy (Strimple 2003), compassion (Harbolt and Ward 2001), and parenting skills (Britton and Button 2006;Turner 2007). Human participants in these studies have also demonstrated decreased social isolation, increased social contact, and increased corrective social interactions (Fournier et al 2007;Messent 1983;Sachs-Ericsson et al 2002;Serpell 2003;Strimple 2003).…”
Section: Human-animal Interaction (Hai) For Military Personnel and Vementioning
confidence: 99%